Presynaptic GLP‐1 receptors enhance the depolarization‐evoked release of glutamate and GABA in the mouse cortex and hippocampus. (19th December 2017) - Rebosio, Claudia; Balbi, Matilde; Passalacqua, Mario; Ricciarelli, Roberta; Fedele, Ernesto
Abstract: Glucagon‐like peptide‐1 receptors (GLP‐1Rs) have been shown to mediate cognitive‐enhancing and neuroprotective effects in the central nervous system. However, little is known about their physiological roles on central neurotransmission, especially at the presynaptic level. Using purified synaptosomal preparations and immunofluorescence techniques, here we show for the first time that GLP‐1Rs are localized on mouse cortical and hippocampal synaptic boutons, in particular on glutamatergic and GABAergic nerve terminals. Their activation by the selective agonist exendin‐4 (1–100 nM) was able to increase the release of either [ 3 H]d ‐aspartate or [ 3 H]GABA. These effects were abolished by 10 nM of the selective GLP1‐R antagonist exendin‐3 (9–39) and were prevented by the selective adenylyl cyclase inhibitor 2′, 5′‐dideoxyadenosine (10 µM), indicating the involvement of classic GLP‐1Rs coupled to Gs protein stimulating cAMP synthesis. Our data demonstrate the existence and activity of presynaptic receptors for GLP‐1 that could represent additional mechanisms by which this neurohormone exerts its effects in the CNS. © 2017 BioFactors, 44(2):148–157, 2018